The Authority of the Ombudsman of the Republic of Indonesia in Handling Maladministration in Public Services: A State Administrative Law Perspective - Daud Renata Candra Ramadan; Indah Sri Utari (Law Research Review Quarterly, 2026)
The consequence of the welfare state concept requires the government to provide excellent public services for the community. To oversee the implementation and prevent maladministration, the state established the Ombudsman of the Republic of Indonesia through Law Number 37 of 2008. Legal issues that arise in state administration practice are the end product of the Ombudsman's authority in the form of "Recommendations" which are only magistrature of influence (Moral Influence) and do not have the force of execution like a court decision. This results in these recommendations often being ignored by state administration agencies. This research is a normative legal research that uses a statute approach and a conceptual approach. Based on the perspective of State Administrative Law, the results of the research itself indicate that the position of the Ombudsman is as an external supervisory institution (state auxiliary organ) tasked with maintaining bureaucratic compliance with the General Principles of Good Governance (AUPB). To address the weak legal binding power of the Recommendation, a legal construction with integrity is needed. This ideal construction is built by synchronizing the Ombudsman Law with the administrative sanction instruments in Law Number 25 of 2009 concerning Public Services and also Law Number 30 of 2014 concerning Government Administration. Through this construction, the act of ignoring the Recommendation itself is categorized as a violation of the AUPB, thus mandatorily forcing the reported official's superior, under the supervision of the Government Internal Supervisory Apparatus (APIP), to impose administrative sanctions on personnel in stages to ensure certainty of resolution.